Application of Project Based Learning Method in Improving Students' Learning Motivation in Islamic Religious Education Lessons - Andriani, Andriani; Masita, Masita; Missouri, Randitha (Yayasan Indonesia Emerging Literacy Education, 2025)
This study aims to analyze the effectiveness of the implementation of Project Based Learning (PJBL) in Islamic Religious Education (PAI) learning at SMPN 15 Kota Bima. The main focus of this study is to assess the extent to which the PJBL method can improve students' understanding of religious concepts, learning motivation, and critical and collaborative thinking skills. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The data obtained were analyzed using a data reduction approach, data presentation, and conclusion drawing to obtain a comprehensive picture of the implementation of PJBL in PAI learning. The results of the study indicate that the PJBL method contributes positively to increasing student involvement in learning. Students become more active in exploring Islamic values ​​and applying them in everyday life through designed projects. In addition, the use of PJBL has been proven to be able to increase student learning motivation by providing a more interactive and applicable learning experience. However, several challenges were identified in the implementation of this method, such as less than optimal time management, teacher readiness in designing appropriate projects, and uneven student involvement in group work.